Teaching Islamic Studies for Inclusive Citizenship in Indonesia and the United States of America: Teachers’ Perspectives - Raihani, Raihani (POTENSIA: Jurnal Kependidikan Islam, 2025)
This research is aimed at investigating the role of Islamic studies in promoting inclusive citizenship in the context of Islamic schools in Indonesia and the United States. Islamic schools have been seen in a rather negative or pessimistic manner due to the sweeping accusation of them being a place for Islamic conservatism. Meanwhile, the currently increasing diversity of society inspirits citizenship to be more inclusive, not only does the state impose equality amongst citizens, but also citizens develop respect and solidarity to others. Through this qualitative research conducted in both contexts, this study found that Islamic studies to a larger extent were designed to educate students to become inclusive citizens. Islam introduced in the textbooks in a weekend Islamic school in the US looks more open to a deeper interreligious relationship because, as a minority, Muslims are eager to display a more friendly Islam to respond to social demands and stigmatization. This study confirms anthropological studies that argue for the plurality of Islam in the domains of interpretations and practices bounded in historical, social and political contexts.